HIV/AIDS and the experience of a Canadian NGO and another Brazilian - Castro-Silva, Carlos Roberto; Hewitt, W. E. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
People living with HIV/AIDS (PHA) have been facing many difficulties in their lives because they are discriminated in various contexts, such as family, community, and work. Currently, AIDS Non-Governmental Organizations (AIDS/NGOs) have become increasingly important because, beyond providing traditional social support, they also offer an environment where PHA may openly express and share not only their experiences with HIV/AIDS, but they can change their personal and professional projetcts. We analyzed historical documents, in-depth interviews, and questionnaires answered by community members within two AIDS/NGOs, one in London, Ontario, Canada (NGO-Ca) and another in Greater Sao Paulo, Brazil (NGO-Br). In this article, some pathways of political participation, which are relevant to both communities, are discussed. Surely, this may contribute to the decreasing of stigma and discrimination related to HIV/AIDS: compassion and altruism as a bridge to political participation, effects on activism, and fostering based on solidarity and co-responsibility are also important discussed issues.